Earth Work 1979 - Toh, Charmaine (National Gallery Singapore, 2016)
Earth Work, originally staged at the National Museum Art Gallery in 1980 by Singapore artist Tang Da Wu, was one of the earliest exhibitions of land art in Singapore. Key works from the exhibition included Gully Curtains, Product of the Sun and Me and Product of the Rain and Me. Earth Work 1979 is a restaging of selected works from the seminal 1980 exhibition. This catalogue delves deeper into Tang's practice, the circumstances of the creation of his earth works and the environment of Singapore in the 1970s and 1980s through essays, interviews, newspaper articles and never-before-seen photo documentation.